2004
DOI: 10.1289/ehp.7143
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Exposure and Colorectal Cancer Risk

Abstract: Organochlorine compounds have been linked to increased risk of several cancers. Despite reductions in their use and fugitive release, they remain one of the most important groups of persistent pollutants to which humans are exposed, primarily through dietary intake. We designed a case–control study to assess the risk of colorectal cancer with exposure to these chemicals, and their potential interactions with genetic alterations in the tumors. A subsample of cases (n = 132) and hospital controls (n = 76) was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 36 publications
1
40
2
1
Order By: Relevance
“…26 Part of these differences may be attributed to differences in exposure to compounds associated with the intake of calcium or dairy products, such as vitamin B2 and organochlorines. 44 Indeed, the association with vitamin B2, a cofactor in folate metabolism, 30 tended to be stronger than the association with calcium in our study, and organochlorines, that none of the aforementioned studies assessed, were associated with K-ras mutations in other tumours. 44 Inconsistent findings were also observed regarding other factors, including consumption of red meat, 26,28,29,38,43 and intake of fat 26,29,40,42 and folate.…”
Section: Discussioncontrasting
confidence: 54%
“…26 Part of these differences may be attributed to differences in exposure to compounds associated with the intake of calcium or dairy products, such as vitamin B2 and organochlorines. 44 Indeed, the association with vitamin B2, a cofactor in folate metabolism, 30 tended to be stronger than the association with calcium in our study, and organochlorines, that none of the aforementioned studies assessed, were associated with K-ras mutations in other tumours. 44 Inconsistent findings were also observed regarding other factors, including consumption of red meat, 26,28,29,38,43 and intake of fat 26,29,40,42 and folate.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, other investigators have found that different chemicals and insecticides pollute water and sediments [17][18][19].…”
Section: Journal Of Adenocarcinoma Issn 2572-309xmentioning
confidence: 73%
“…The tandem increase in both seric pro-inflammatory cytokines IL-6 and TNFa and increase in tissue levels of P-selectin and b-catenin is consistent with the recent report of Zhang et al (2015) noting increased P-selectin in the plasma and IL-1b in the sub-endothelial layer of the abdominal aorta in rats treated with 5 or 10 mg ENDO/kg/day. Although Howsam et al (2004) correlated exposure to OC pesticides, such as ENDO, with a risk of colon cancer. Bedor et al (2010) also reported on the carcinogenic potential of these compounds.…”
Section: Discussionmentioning
confidence: 99%